Regarding issues that affect the execution of permanent retaining wall - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the issues that affect the execution of permanent retaining wall of BRACU new campus project.